Formulation And Characterization Of Buccal Film Nanoemulsion Apigenin As Antidiabetic - Ardianes Firmansya; Fajar Setiawan; Lusi Nurdianti; Anna Yuliana (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
Apigenin (4`,5,7-trihydroxyflavone) is a flavonoid of subclass flavones that have antidiabetictherapeutic activity but limitations BCS Class II low solubility of 2.16 μg/L. To overcome theselimitations, the development of nanoemulsion formulation technology, increasing solubility increasesdissolution, absorption and bioavailability. It is incorporated into the buccal film for easy applicationand direct access to the systemic circulation. This study aims to obtain apigenin nanoemulsion withthe best characterization and buccal film that meets the characterization. The method was carried outexperimentally in the manufacture of nanoemulsions by spontaneous emulsification, a buccal filmby solvent casting, and the characterization. 10 nanoemulsion formulas met the characterizationwith globule size <20.34nm, polydispersity index <0.131, zeta potential close to 0mV, pH 6.23-6.59, %transmittance close to 100% and best F10 incorporated into buccal film has 29x the solubilitycompared to apigenin with p≤0.05. All buccal films met the characterization with F3 having a 2x fasteronset of release than F1&F2 with 86.07% diffusion and 97.9333 mg/sheet. Thus, it was concludedthat the formulation and characterization of buccal film fulfilled the characterization and F10 apigeninnanoemulsion increased the solubility 29-fold with the buccal film F3 having a faster onset of release.